PENINGKATAN KOMPETENSI KEPEMIMPINAN DAN MOTIVASI SISWA MELALUI LDKS DAN SEMINAR BAGI ORGANISASI SISWA SMPN 2 WAGIR - Rofiah, Laila; Masalah, Wafiyatu; Nurchorin, Resa Ayu; Ekayanti, Yunita; Nisa, Faradina Fahrun; Islam, M. Fasichul; Salshabilla, Narita; Aliyah, Silfina Karomatul (Jurnal Edukasi Pengabdian Masyarakat, 2025)
This community service program aimed to enhance the leadership competencies and motivation of the student administrators of OSIS (Student Council), PMR (Youth Red Cross), and Pramuka (Scouts) at SMPN 2 Wagir. The activity was based on the school's need to equip students with skills in leadership, discipline, teamwork, and social awareness. Held from September 12–14, 2025, this program combined the Basic Student Leadership Training (LDKS) method, which included simulations and outbound activities, with a leadership and motivational seminar featuring academics and practitioners. The evaluation results indicated an improvement in students' communication skills, self-confidence, discipline, and motivation to participate in organizations. Specifically, OSIS members became more skilled in organizational management, PMR members in social awareness, and Pramuka members in discipline and teamwork. The program proved to make a positive contribution to strengthening the character of students at SMPN 2 Wagir.